2013
DOI: 10.1080/02626667.2013.854368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of watershed subdivision level on semi-distributed hydrological simulations: case study of the SLURP model applied to the Xiangxi River watershed, China

Abstract: -P., 2013. Effects of watershed subdivision level on semi-distributed hydrological simulations: case study of the SLURP model applied to the Xiangxi River watershed, China. Hydrological Sciences Journal, 59 (1), 108-125. Abstract This study investigates the impacts of watershed subdivision on hydrological simulations. The SLURP (Semi-distributed Land Use-based Runoff Processes) model was employed in the Xiangxi River watershed, China, with eight watershed subdivision schemes. Under each scheme, the SLURP mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
(46 reference statements)
1
18
0
Order By: Relevance
“…Increasing the number of sub-watersheds definitely increases input data preparation, computational time and calibration effort; therefore, the sub-watershed-average inputs generated from gauging stations vary with different watershed subdivisions [17]. Several authors discuss how variations in the distributed model inputs result in various levels of watershed subdivision.…”
Section: Overview Of Schematization and Parameterization Approaches Imentioning
confidence: 99%
“…Increasing the number of sub-watersheds definitely increases input data preparation, computational time and calibration effort; therefore, the sub-watershed-average inputs generated from gauging stations vary with different watershed subdivisions [17]. Several authors discuss how variations in the distributed model inputs result in various levels of watershed subdivision.…”
Section: Overview Of Schematization and Parameterization Approaches Imentioning
confidence: 99%
“…They showed that (semi-)distributed models are usually more suitable for the representation of landscape heterogeneity and the exploration of hydrological processes, and are also more able to reproduce observed discharge dynamics than lumped models Euser et al, 2015). However, there is a threshold of subdivision level above which no more improvements can be achieved (Wood et al, 1988;Han et al, 2014;Haghnegahdar et al, 2015). On the other hand, natural variability outside the models' spatial discretisation level can still exhibit an important limitation in the representation of natural processes.…”
Section: Discretisation Approaches In Semi-distributed Hydrological Mmentioning
confidence: 99%
“…the spatial resolution) of hydrological models, partly also as a user decision during the pre-processing process, has long been acknowledged in numerous studies (e.g. Wood et al, 1988;Kumar et al, 2010;Han et al, 2014;Euser et al, 2015;Haghnegahdar et al, 2015;González et al, 2016). For gridbased models, this influence has been thoroughly assessed (e.g.…”
mentioning
confidence: 99%
“…The vertical water balance concept applied to each land type within an ASA is four nonlinear tanks, i.e. canopy storage, snow storage, fast storage and slow storage, representing canopy interception, snowpack, aerated soil storage and groundwater, respectively (Han et al, 2014). In SLURP, water balance equation is expressed as: where Dt is the time step, S soil,t is the soil moisture at the time t; P pre,t , M sno,t , E evap,t and Q gr,t refer to accumulated rainfall, snowmelt, evapotranspiration and recharge to groundwater, respectively.…”
Section: Hydrological Modelmentioning
confidence: 99%